A gift of time: the contemporary artist-in-residency programme - Hutchens, J (2021)

(untitled)
Contemporary artist residency programmes around the globe have proliferated since the early 1990s. Promoted through new online platforms such as Res Artis and TransArtists, they are now firmly embedded within artistic networking and discursive practices. Whereas residency programmes were originally valued for their role in enabling mobility and cultural exchange, this thesis addresses a countervailing tendency that identifies residencies as retreats, whose primary role is to shelter artists from external pressures and demands. Residency programmes frequently claim to provide artists with a ‘gift of time’, or even more commonly, to provide ‘time and space.’ This thesis identifies the concept of providing temporal-spatial withdrawal as a ‘problem-idea’ that courses through and also shapes residency programmes and discourses: in practice, the emphasis on withdrawal can occlude the real pressures and demands that residencies place on artists, the complexity of their entanglements within the wider art world and its institutions, and the extent to which artistic practices and residency practices are intertwined. The thesis is structured through an analysis of some of the main types of artist residencies, since these are also related to the key concepts that shape contemporary residency thinking. The first part examines residency programmes within museums, which are frequently used to reinscribe the concept of the museum as a patron and supporter of living artists. The second part focuses on retreat-type residencies, programmes that actively promote the ‘gift of time’ idea by offering to ‘shelter’ artists in rural and remote places. The final part addresses discourses on artistic labour, together with case studies of experimental residency models, in order to consider the different ways that residencies ameliorate, contribute to, and make visible, contemporary conditions for artistic working. One of the aims of the thesis is to challenge the tendency of residency programmes to disavow their own institutional character. This requires that we acknowledge the extensive infrastructure of contemporary residency programmes and the ways in which they actively shape contemporary artistic production.